PELAKSANAAN ADMINISTRASI SEWA GEDUNG PADA PT. POS INDONESIA - Khotimah Herliana; Alya Prazna Pundarika (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
Administration is a collaborative process carried out by two or more people to achieve acommon goal. This administrative activity is very necessary from the time people are born untilthe end of their lives. Meanwhile, according to Pratama (2020) what is meant by administrativeactivities is a series of arrangements that occur between two or more people who have made ajoint agreement to achieve common interests. Administrative implementation carried out by PT.POS Indonesia has been computerized using a barcode scan, this is done for the effectivenessand efficiency of carrying out administrative records from the entry and exit of Warehousegoods. PT. POS Indonesia not only rents Warehouse space to other logistics companies, but alsoimplements a computerized administration system so that it is more effective and more efficientin terms of implementation in the field. This study uses the observation method, in order to beable to directly see the process of administrative activities carried out by PT. POS Indonesia inthe field.